Socio-Economic Profile of Dairy Farmers in Maharashtra: A Case Study of Latur District (Global Journal of Science Frontier Research, 2023)
If we look at the state s population growth patterns milk and milk products must be used to ensure both food security and nutritional security Another possibility is that the populace expresses various concerns like food insecurity perceived insecurity unemployment etc and the government responds by taking quick and effective action to address these concerns The current study examines various facets of dairy farming and the current state of milk production consumption and sales The city of Latur was deliberately chosen for the investigation Two tehsils were randomly chosen from the zone and two blocks were randomly chosen from each tehsil
Keywords: dairy farmers; socio-economic profile; occupation; rural development